The servicification of manufacturing in Asia: Redefining the sources of labor productivity - Valerie Mercer-Blackman; Christine Ablaza (Asian Development Bank Institute (ADBI), 2018)
Services are playing an increasingly important role in the global economy. Over the last few decades, the sector's contribution to output, employment, and value-added trade has grown quite dramatically. The rise of services and apparent decline of manufacturing employment have raised concerns about the future of growth given the lower labor productivity of the former. But more recent studies have argued against this for several reasons. Among others, current measures of productivity do not properly account for the indirect contribution of services to other sectors. For example, the additional value generated by services in the production of manufactured goods can be substantial, but it is not properly accounted for because of the indivisible and intangible nature of services. Moreover, the rise of the digital economy has created new ways for services to contribute to production. This paper aims to tackle some of these issues by focusing on the servicification of manufacturing in Asia. Our contribution to the emerging literature is twofold. First, we propose a conceptual framework of servicification. And second, we offer some preliminary evidence of this phenomenon for Asia and measurement proposals to disentangle the contribution of services to labor productivity.
Keywords: F14; F23; F63; J22; L80; C80; 330; servicification; premature deindustrialization; labor productivity; manufacturing; time use surveys; global value chains